Tinjauan Historis Jam’ul Qur’an Hingga Masa Digitalisasi Angka - Nandani Zahara Mahfuzah; Milhan (CV. ITTC INDONESIA, 2024)
The purpose of this study is to determine the historical review of jam'ul qur'an to the digitalized numbers. Jam'ul Qur'an until the period of digitization of numbers, it can be concluded that the process of collecting, copying, and writing the Qur'an has undergone significant developments throughout Islamic history. In this research using qualitative research method is a research approach that aims to respond to phenomena with the aim of understanding the experiences experienced by research participants. Starting from the time of the Prophet Muhammad SAW to the time of the Khulafaur Rashidin, Abu Bakar Ash-Shiddiq, Uthman bin Affan, and so on, the leaders and companions of the Prophet played an important role in preserving and writing the Qur'an. With various forms of digitization such as Qur'ānic apps, websites, and ancient manuscript digitization projects, access to the Qur'ān has become easier and wider than ever before. This allows Muslims around the world to better read, study and understand Islam's sacred texts, as well as deepen their spiritual connection with Allah SWT.